2023
DOI: 10.21203/rs.3.rs-2989980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of virulence genes and in-vitro biofilm production in clinical multidrug resistant Escherichia coli in Dakar Senegal

Abstract: Background Bacterial virulence is a key factor determining the outcome of each bacterial infection and virulent bacteria are often associated to high-risk infections. Extraintestinal pathogenic Escherichia coli (ExPEC) is the most implicated bacterium in human bacterial infections and its virulence factors are classified into five categories: adhesins, toxins, iron capture systems, protectins and invasins. Furthermore, bacterial biofilms are the main cause of hospital-acquired infections like urinary catheter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 97 publications
2
2
0
Order By: Relevance
“…The presence of virulence factors (genes) with the ability of UPEC to form biofilms in vitro has been reported [27,28,30,35,69,73]; nevertheless, the quantitative correlation between biofilm and virulence factors has yielded different results. In agreement with previous studies [21,29,30,69,74,76,[80][81][82], strong biofilm-producing strains presented a higher prevalence of fimH and papC genes. Indeed, fimH, the gene coding for the α-Dmannose-specific tip adhesin of type 1 fimbriae, was present in almost all the strains, denoting their important role in adhesion and biofilm formation in UPEC.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The presence of virulence factors (genes) with the ability of UPEC to form biofilms in vitro has been reported [27,28,30,35,69,73]; nevertheless, the quantitative correlation between biofilm and virulence factors has yielded different results. In agreement with previous studies [21,29,30,69,74,76,[80][81][82], strong biofilm-producing strains presented a higher prevalence of fimH and papC genes. Indeed, fimH, the gene coding for the α-Dmannose-specific tip adhesin of type 1 fimbriae, was present in almost all the strains, denoting their important role in adhesion and biofilm formation in UPEC.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have reported a prevalence of 78% [71], 80% [31,72], and 84.3% [73]. Most strains were able to form moderate biofilms, which is consistent with previous work [21,29,30,73]. Several studies have shown a lower frequency of moderate biofilm-forming strains and a higher prevalence of weak biofilm-producing strains [18,73,74].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations